Development of Instruments for Assessing Linguistic Intelligence in Elementary Schools - Maharani, Dea Sinta; Kurniaman, Otang; Noviana, Eddy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
Linguistic intelligence is one of eight multiple intelligences that currently attracts attention in the world of education. Linguistic intelligence is a person's ability to speak both verbally and in writing, besides that people who have linguistic intelligence also master the components of linguistic intelligence which consists of phonology, syntax, semantics and pragmatics. The typeof research used is research and development (R & D) with a 4D model. The subjects in this study were experts as validators, fifth grade students for trials and homeroom teachers in elementary schools. Data collection is done by giving a questionnaire to the validator. In this study the researchers concluded that the product of the developed linguistic intelligenceassessment instrument was declared feasible to be used based on the results of validation of 86% with very feasible categories. The obstacle in developing the product of this instrument of linguistic intelligence assessment is the lack of knowledge of the school about the importance of linguistic intelligence for students in elementary schools.